2018
DOI: 10.1186/s40816-018-0077-8
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic activity of Piper sylvaticum Roxb. (family: Piperaceae): In vitro and in silico studies

Abstract: Background: The present study was conducted to investigate the anthelmintic activity of methanol extract of Piper sylvaticum stem (MEPSS) in experimental model followed by in silico molecular docking study and ADME/T analysis. Methods: Anthelmintic activity was determined by an aquarium worm (Tubifex tubifex). Then, molecular docking study was performed to identify compounds having maximum activity against TUBULIN-COLCHICINE enzymes by using Schrödinger-Maestro v 10.1 docking fitness. Additionally, ADME/T prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Again, it gives us not only the possible mechanism of action of a protein or enzyme but also the binding moods inside the binding site of proteins or enzyme. So, we have also used the molecular docking of some compounds of P. chaba to make a collaboration between this compounds and different types of enzymes responsible for inflammation to illustrate the biochemical process of the antiinflammatory activity [32][33][34]. These compounds were docked against three targets which were COX-1 (PDB ID: 2OYE), COX-2 (PDB ID: 6COX) and NF-κβ (PDB ID: 5LDE).…”
Section: Discussionmentioning
confidence: 99%
“…Again, it gives us not only the possible mechanism of action of a protein or enzyme but also the binding moods inside the binding site of proteins or enzyme. So, we have also used the molecular docking of some compounds of P. chaba to make a collaboration between this compounds and different types of enzymes responsible for inflammation to illustrate the biochemical process of the antiinflammatory activity [32][33][34]. These compounds were docked against three targets which were COX-1 (PDB ID: 2OYE), COX-2 (PDB ID: 6COX) and NF-κβ (PDB ID: 5LDE).…”
Section: Discussionmentioning
confidence: 99%
“…A cubic box of specific dimensions centered on the centroid of the active site residues was generated for the receptor. The bounding box was set to 14 Å × 14 Å × 10 Å and it's essential to identify the active binding site in the target protein [29].…”
Section: Grid Generationmentioning
confidence: 99%
“…Additionally, a quantitative phytochemical analysis of MEPSL also reported that it contains substantial amounts of phenol (65.83 mg gallic acid equivalent/g dried extract), flavonoids (102.56 mg quercetin equivalent/g dried extract), and condensed tannins (89.32 mg catechin equivalent/g dried extract). Furthermore, MEPSS contains significant amounts of phenol (93.39 mg), flavonoids (53.74 mg), and condensed tannins (55.82 mg) [9,11,14]. On the other hand, a previous acute toxicity study described that the plant had no mortality, abnormal behavior, and neurological changes up to 2000 mg/kg dose, which is a clear indication that the plant extract has low toxicity profile and is safe for a therapeutic dose [11].…”
Section: Resultsmentioning
confidence: 97%
“…Kumar et al reported antioxidant activity of the roots and fruits [13]. Paul et al reported the anthelmintic activity of stem [14] and Haque et al described the antidiarrheal activity of the stem [15]. Chy et al stated that the plant (stem) has anti-nociceptive and anti-inflammatory properties [11].…”
Section: Introductionmentioning
confidence: 99%